Proteomic Data and Drug Implications for Cerebral Microvascular Endothelial Cells Under Varying Oxygen Levels - Sarah Barakat; Fan Yang; Hayriye Ecem Yelkenci; Kıvanç Kök; Giovanni E. Mann; Emrah Eroğlu (Scientific Data)
Abstract Hyperoxia in standard cell cultures (18 kPa O2) imposes cellular oxidative stress, potentially skewing research and drug screening outcomes. Cerebral microvascular endothelial cells (hCMEC/D3) experience no more than 7 kPa O2 in vivo. In this study, hCMEC/D3 cells were adapted to 5 kPa O2 for 5 days to optimize an in vitro physiological cell culture model. Using a SYNAPT G2-Si mass spectrometer, we compared the proteomic profiles of cells cultured under 5 kPa versus 18 kPa O2. A substantial proteomic shift under hyperoxia highlighted the strong impact of oxygen levels on protein expression. We further investigated the effect of oxygen levels on drug screening using sulforaphane (SFN), an inducer of NRF2-regulated antioxidant defense genes. SFN induced more pronounced changes in proteomic profiles under 18 kPa O2 compared to 5 kPa, indicating oxygen-dependent cellular drug responses. This dataset offers a valuable resource for analyzing oxygen-sensitive proteomic changes. Comparative studies using different drugs or cell types could further elucidate oxygen-dependent signaling and inform the development of therapies aligned with physiological oxygen levels.